2009
DOI: 10.2807/ese.14.42.19369-en
|View full text |Cite
|
Sign up to set email alerts
|

Interim report on pandemic H1N1 influenza virus infections in South Africa, April to October 2009: Epidemiology and factors associated with fatal cases

Abstract: We provide an interim report on pandemic H1N1 influenza activity in South Africa, with a focus on the epidemiology and factors associated with deaths. Following the importation of the virus on 14 July 2009, and the epidemic peak during the week starting 3 August, the incidence in South Africa has declined. A total of 12,331 cases and 91 deaths have been laboratory-confirmed as of 12 October 2009. Age distribution and risk groups were similar to those observed elsewhere. The median age of patients who died (33.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 4 publications
3
64
1
Order By: Relevance
“…Although this percentage is higher than the national HIV prevalence (7%) ( 11 ), the HIV-positive patients were all from Nyanza Province, which has an HIV prevalence of 15% ( 11 ). Nevertheless, our findings suggest that HIV patients could be at risk for severe pandemic (H1N1) 2009 influenza, supporting results of a study in South Africa which reported that 53% of pandemic (H1N1) 2009 patients who died were HIV positive ( 12 ). However, our report included a relatively small number of patients who had been tested for HIV, and CD4 counts and information on use of antiretroviral drugs were unavailable.…”
Section: Discussionsupporting
confidence: 90%
“…Although this percentage is higher than the national HIV prevalence (7%) ( 11 ), the HIV-positive patients were all from Nyanza Province, which has an HIV prevalence of 15% ( 11 ). Nevertheless, our findings suggest that HIV patients could be at risk for severe pandemic (H1N1) 2009 influenza, supporting results of a study in South Africa which reported that 53% of pandemic (H1N1) 2009 patients who died were HIV positive ( 12 ). However, our report included a relatively small number of patients who had been tested for HIV, and CD4 counts and information on use of antiretroviral drugs were unavailable.…”
Section: Discussionsupporting
confidence: 90%
“…A case series of patients who died during the 2009 influenza pandemic in South Africa described underlying tuberculosis in 10% of deaths which was greater than the population prevalence of tuberculosis [31]. Another study from South Africa showed that patients co-infected with tuberculosis and influenza as compared to patients with tuberculosis only were at increased risk of death (adjusted relative risk ratio (aRRR) 3.2 95% CI 1.1–10.0).…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization estimated approximately 16,000 deaths between April 2009 and January 2010. The majority of these deaths corresponded to patients with underlying risk factors, such as metabolic dysfunctions, pregnancy, obesity and immunosuppression, contributing to worse outcomes [24,25]. …”
Section: Microbial Etiology Of Community-acquired Pneumonia (Cap)mentioning
confidence: 99%